1996
DOI: 10.1073/pnas.93.22.12519
|View full text |Cite
|
Sign up to set email alerts
|

Amphipathic domains in the C terminus of the transmembrane protein (gp41) permeabilize HIV-1 virions: a molecular mechanism underlying natural endogenous reverse transcription.

Abstract: Reverse transcription of HIV-1, without detergent or amphipathic peptide-induced permeability of the viral envelope, has been demonstrated to occur in the intact HIV-1 virion. In this report, we demonstrate that the amphipathic domains in the C terminus of the transmembrane glycoprotein (gp4l) account for the natural permeability of the HIV-1 envelope to deoxyribonucleoside triphosphates, the substrates for DNA polymerization. In addition, nonphysiological deoxyribonucleoside triphosphates, such as 3'-azido-3'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
42
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 43 publications
(25 reference statements)
4
42
0
Order By: Relevance
“…The results obtained here confirmed the findings of Zhang et al (37), demonstrating that the amphipathic domain of the gp41 transmembrane glycoprotein is responsible for the passage of dNTPs from the outside medium to the interior of the virions. Due to this, the increase in the basal levels of RT activity in response to an increase in the dNTP concentration was not detected in nonenveloped or even pseudotyped HIV-1 particles carrying the MLV envelope proteins.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results obtained here confirmed the findings of Zhang et al (37), demonstrating that the amphipathic domain of the gp41 transmembrane glycoprotein is responsible for the passage of dNTPs from the outside medium to the interior of the virions. Due to this, the increase in the basal levels of RT activity in response to an increase in the dNTP concentration was not detected in nonenveloped or even pseudotyped HIV-1 particles carrying the MLV envelope proteins.…”
Section: Discussionsupporting
confidence: 82%
“…This has been termed NERT to distinguish it from the somewhat artificial process that takes place in standard ERT assays (36). NERT is made possible by the amphipathic domains of the gp41 transmembrane protein, which render the HIV-1 envelope permeable to a range of small molecules, such as deoxynucleoside triphosphates (dNTPs) (37). NERT is an active process that is responsive to the virion microenvironment.…”
mentioning
confidence: 99%
“…The tagged AGO1 or AGO2 was then inserted into pcDNA3.1 vector. A series of deletion mutants of MOV10 were generated via PCR-based mutagenesis, as we have described previously (16). The miRNA reporter constructs used in this study (psi-per-mir16 and psi-per-mir25) were generated by direct insertion of the annealed corresponding miRNA-binding sites into the 3Ј-UTR region of Renilla luciferase gene in psi-CHECK-2 vector (Promega) between XhoI and NotI sites.…”
Section: Methodsmentioning
confidence: 99%
“…9-14 This process can even occur in the absence of added detergent (referred to as natural endogenous reverse transcription or NERT). [15][16][17] However, the yield of completed products in ERT and NERT reactions is extremely low. It can be concluded that the virion environment is not sufficient to allow efficient replication or that certain cellular components or structural alterations are essential for efficient replication.…”
Section: Introductionmentioning
confidence: 99%